#### Answer

$\frac{4}{9}$

#### Work Step by Step

$(-\frac{2}{3})^2=(-\frac{2}{3})\times(-\frac{2}{3})=\frac{2\times2}{3\times3}=\frac{4}{9}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$\frac{4}{9}$

$(-\frac{2}{3})^2=(-\frac{2}{3})\times(-\frac{2}{3})=\frac{2\times2}{3\times3}=\frac{4}{9}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.